2020
DOI: 10.1111/tpj.14706
|View full text |Cite
|
Sign up to set email alerts
|

A long non‐coding apple RNA, MSTRG.85814.11, acts as a transcriptional enhancer of SAUR32 and contributes to the Fe‐deficiency response

Abstract: SummaryIron (Fe) is an essential plant nutrient and its deficiency typically limits plant growth. Long non‐coding (lnc) RNAs are involved in adaptive responses to nutrient stress; however, it is not known whether they function in the regulation of the canonical Fe‐deficiency response. The expression of Malus domestica (apple) lncRNA MSTRG.85814 is induced by Fe deficiency, as identified by high‐throughput strand‐specific RNA‐seq analysis of an apple homograft system. MSTRG.85814 has a complex structure, with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 97 publications
0
45
0
Order By: Relevance
“…Apples are dicotyledons that adopt the typical Mechanism I strategy to absorb and translocate Fe (Zhang et al 2019;Zhou et al 2019). Under Fe de ciency stress, rst, plants develop a proton pump that acidi es the rhizosphere to increase the solubility of Fe through the upregulation of plasma membrane (PM) H + -ATPase (AHA) family genes, such as CsAHA1, AtAHA2, and MdAHA8 (Sun et al 2020;Zhao et al 2016). In the present study, we found that rhizosphere pH was signi cantly reduced, whereas the activity of H + -ATPases increased after exogenous Res was applied under Fe de ciency stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apples are dicotyledons that adopt the typical Mechanism I strategy to absorb and translocate Fe (Zhang et al 2019;Zhou et al 2019). Under Fe de ciency stress, rst, plants develop a proton pump that acidi es the rhizosphere to increase the solubility of Fe through the upregulation of plasma membrane (PM) H + -ATPase (AHA) family genes, such as CsAHA1, AtAHA2, and MdAHA8 (Sun et al 2020;Zhao et al 2016). In the present study, we found that rhizosphere pH was signi cantly reduced, whereas the activity of H + -ATPases increased after exogenous Res was applied under Fe de ciency stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, M. baccata is sensitive to Fe de ciency stress (Wang et al 2013a). Fe de ciency stress induces chlorosis of M.baccata leaves, decreases tree vigor, and results in huge economic losses (Sun et al 2020). Therefore, the Fe de ciency tolerance of M. baccata seedlings must be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from grafted tissues using an RNAprep Pure Plant Plus Kit (TIANGEN, DP441). Library preparation was as described in our previous study 58 .…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were transformed into GV3101 Chemically Competent Agrobacterium tumefaciens cells (Weidi Biotechnology, AC1001). Positive clones were mixed to give equal concentrations of pTRV 69 and pTRV2, or its derivatives, and introduced into M. domestica, Populus tremula, Solanum lycopersicum and A. thaliana seedlings using vacuum in ltration and injection, respectively 58 . The transformation procedure used a pressure of 0.8 MPa, which was applied twice for 5 min time.…”
Section: Discussionmentioning
confidence: 99%
“…AtR8, which is transcribed from RNA polymerase III, is specifically expressed in the roots of A. thaliana and is involved in the response to hypoxia stress [46]. The apple lncRNA, MSTRG.85814.11, acts as a transcriptional enhancer of SAUR32 and contributes to the Fe deficiency response [47].…”
Section: The Extensive Involvement Of Lncrnas In Plant Growth and Devmentioning
confidence: 99%